BIA‐Obesity (Business Impact Assessment—Obesity and population‐level nutrition): A tool and process to assess food company policies and commitments related to obesity prevention and population nutrition at the national level. (17th July 2019) - Sacks, Gary; Vanderlee, Lana; Robinson, Ella; Vandevijvere, Stefanie; Cameron, Adrian J.; Ni Mhurchu, Cliona; Lee, Amanda; Ng, See Hoe; Karupaiah, Tilakavati; Vergeer, Laura; L'Abbé, Mary; Swinburn, Boyd
Summary: Addressing obesity and improving the diets of populations requires a comprehensive societal response. The need for broad‐based action has led to a focus on accountability of the key factors that influence food environments, including the food and beverage industry. This paper describes the Business Impact Assessment—Obesity and population‐level nutrition (BIA‐Obesity) tool and process for benchmarking food and beverage company policies and practices related to obesity and population‐level nutrition at the national level. The methods for BIA‐Obesity draw largely from relevant components of the Access to Nutrition Index (ATNI), with specific assessment criteria developed for food and nonalcoholic beverage manufacturers, supermarkets, and chain restaurants, based on international recommendations and evidence of best practices related to each sector. The process for implementing the BIA‐Obesity tool involves independent civil society organisations selecting the most prominent food and beverage companies in each country, engaging with the companies to understand their policies and practices, and assessing each company's policies and practices across six domains. The domains include: "corporate strategy, " "product formulation, " "nutrition labelling, " "product and brand promotion, " "product accessibility, " and "relationships with other organisations." Assessment of company policies is based on their level of transparency, comprehensiveness, and specificity, with reference to best practice.